A produção do conhecimento sobre gênero no congresso brasileiro de ciências do esporte (CONBRACE) - LEAL, Deyveson Gama (2022)
The present work presents as a problem: “How are the publications of the articles on Gender in the Proceedings of CONBRACE from 2013 to 2017?” And aims to analyze the configuration of publications on the Gender of Proceedings of the 2013, 2015 and 2015 editions. 2017 of CONBRACE, in order to draw a profile of the most recurrent themes in publications. The specific objectives are respectively: to identify the main categories of analysis of productions related to gender issues in CONBRACE and to identify the theoretical bases that support these productions related to gender published in CONBRACE. The methodological course traced from the approximation with the dialectical historical materialist method. The research was developed from a bibliographic research, whose sources were the Annals of GTT Gender and GTT Inclusion and Differences of the 2013, 2015 and 2017 editions. The results show that the publications on Gender in CONBRACE are configured as works in mostly in the field of phenomenology, followed by publications from the critical-dialectical field. It is concluded at the end of our research that there has been a breakthrough in research on gender issues in CONBRACE, but there is still a need for the expansion of theoretical frameworks around these publications.